The double burden of under- and over-nutrition among school-aged children and adolescents in two Nigerian States - Adeomi, Adeleye Abiodun (My University, 2022)
Introduction: Little data exists on the double burden of malnutrition (DBM) among schoolaged children and adolescents in Nigeria, despite some evidence for its existence. This research explored mothers’ perceptions and cultural beliefs about the concept, causes, and community experience of under- and over-weight children and adolescents and measured the prevalence rates of thinness, underweight, stunting, overweight, obesity to investigate the existence of the DBM. In addition, the research identified individual and contextual correlates of the DBM including food security, dietary diversity and dietary patterns among school-aged children and adolescents in the two Nigerian states. Methods: The study was a community-based study, carried out in Osun and Gombe States in Nigeria. The study used a mixed-methods design, with a sequential exploratory approach. This involved a qualitative study using focus group discussions among 76 women in 8 randomly selected communities in the two Nigerian states, and a subsequent quantitative cross-sectional study carried out among 1,200 (600 in each state) 6 – 19 year olds and their mothers, who were selected using multi-stage sampling technique. Individual (child), household and community level data were collected using structured pre-tested questionnaire, while anthropometric data (weight and height) were collected using weighing scales and stadiometers. Thinness and overweight/obesity, measured using the BMI-for-age Z-scores from the World Health Organization (WHO) growth reference values for 5 – 19 year olds, were used as the indicators for under- and over-nutrition, respectively. Additionally, dietary diversity (DD) was assessed using a 24-hour dietary recall and dietary patterns (DPs) were determined by principal component analysis using a 30-day food frequency questionnaire. Multi-variable analyses were used to identify determinants, while multi-level analyses were performed to understand the influence of the community, and community-level factors on under- and over-nutrition among school-aged children and adolescents in the two selected states. Results: Mothers from the qualitative study expressed perceptions on the concepts, causes and community experience of under- and overweight children and adolescents. Majority of the women reported no known food taboo or restrictions, and no cultural practices relating to the nutrition of children and adolescents. The mean age of the respondents of the cross-sectional study was 11.6 ± 3.8 years. The overall prevalence rate of stunting was 34.9%, underweight was 13.5%, thinness was 10.3% and overweight/obesity was 11.4%, which typifies the DBM at population level. Four percent were both stunted and overweight/obese, typifying individual level DBM. The rates for the indicators of under- and over-nutrition differed significantly across demographic, socio-economic and household/family characteristics (p < 0.05). The random effects of the multilevel analysis showed that the full models accounted for about 82% and 39% of the odds of under-nutrition and over-nutrition across the communities respectively, as explained by the proportional change in variance (PCV). Also, 21.6% and 28.5% of the variation in the odds for under-nutrition and over-nutrition were attributable to community level variables respectively, and these were statistically significant (p < 0.001). The fixed effects showed that household size was positively associated with under-nutrition, while the upper wealth index was inversely associated with under-nutrition. Age, exclusive breastfeeding, physical activity and the upper wealth index were inversely associated with overnutrition, while residing in Osun State, female gender and screen time > 2 hours/day were positively associated with over-nutrition. Two DPs were identified. The diversified DP had positive loadings for all food groups indicating a varied diet, while the traditional DP had positive loading for starchy foods/cereals, legumes and sugars. The traditional DP was positively associated with both under- and overnutrition, while the diversified DP was inversely related with under-nutrition. Conclusions: Gaps and misconceptions exist in the perceptions of mothers on under- and overweight children and adolescents. Food taboos, food restrictions and other cultural beliefs or practices were not reported by majority of the mothers. The study found evidence of DBM at individual and population levels, and the DBM was significantly influenced by the community and individual-level factors. A traditional DP was positively associated with the DBM, while the diversified DP was inversely associated with under-nutrition. Educational programmes for mothers and school-aged children and adolescents should target identified gaps and misconceptions and promote the importance of healthy/diversified dietary patterns. There is a need to explore the possibilities of community-based interventions to combat the double burden of malnutrition.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2022